CGIAR Accredited to UNEA: Bringing Food, Land, and Water Systems into Global Environmental Policy dialogues - Edward-Uwadiale, Regina; Ojanji, Wandera (CGIAR System Organization, 2025)
This article announces that CGIAR—the global agricultural research partnership—has been officially accredited as an intergovernmental organization (IGO) to the United Nations Environment Assembly (UNEA), granting it observer status to participate in UNEA sessions including the upcoming UNEA-7. This accreditation formally integrates CGIAR into the highest level of global environmental governance, strengthening its role as a scientific partner for UN Member States and enabling the organization to bring evidence from agricultural science into environmental policy dialogues. It positions CGIAR to contribute research and recommendations on climate change, biodiversity, land degradation, and sustainable food, land, and water systems, helping bridge gaps between food systems and global environmental goals. The article highlights how this new role enhances CGIAR’s capacity to support coherent policy approaches and advance international commitments under the Paris Agreement, the Global Biodiversity Framework, and land neutrality targets through science-based input and collaboration.